O mapeamento das brincadeiras tradicionais e digitais nos anos iniciais do Ensino Fundamental - Madureira, Isabela Evangelista (2025)
The cultural practices of children's play currently include a range of toys and games that involve New Digital Technologies, which quickly transform and improve. The technological apparatus, with its incessant growth, interferes in the way children play, a factor that directly influences the general culture, which, in turn, influences the playful culture of children. In this sense, the research presented aims to map the games of children in the 3rd year of a public school in the capital of the state of Tocantins, Palmas. The methodological approach is qualitative and a bibliographical and field research will be carried out, having as analysis the method of Discursive Textual Analysis. For the investigation, children aged between 8 and 9 who are enrolled in the 3rd year of the researched school will be considered as research subjects. For data collection, semi-structured interviews and non-participatory observation will be carried out based on a script planned with the children. In addition to the scientific production of articles, the final product of the elaboration of this dissertation will be a digital educational material. Finally, it is believed that traditional and electronic games will form part of children's play activities in modern society.